REALISASI KEUANGAN DANA PERIMBANGAN REGIONAL DI NDONESIA - Tanjung, Abdi; Handra, Hefrizal; Yonnedi, Efa (Jurnal Paradigma Ekonomika, 2022)
Theory federalism preservation market emphasize importance decentralization and incentive government on development market. This article explores the definition of financial realization of balancing funds embedded in the vision compete for regional finance in Indonesia. its activities are oriented towards the free market in Indonesia imagine expansion framework regulation in whole cleavage earth, promises better financial services, credit and investment in the country in exchange for strong financial property protection and (implicitly) by dramatic reduce autonomy policy finance for government area. The central government will certainly promote strict state management of foreign and domestic investors, populist redistribution, and increasing dependence on non-financial transactions market. Indonesia's regional finance project will unite regions through regional physical infrastructure and capitalist financial markets while maintaining the a public sector bank that is responsive to central government priorities. Approach in every area will emphasize on needs government for authority financial policy and with this approach attention to predictability regulation and deepening finances will be better in the future. Equality is usually not a term associated with competing designs for finance. But the understanding that contrast about what is needed to improve the set of rules that govern saving savings and provision credit almost always involve conceptualization implicit or explicit about equality and justice.